Case report: Novel compound heterozygous missense mutations in the DDHD2 gene in a Chinese patient associated with spastic paraplegia type 54 - Xu, Xin; Lu, Fen; Du, Senjie; Zhao, Xiaoke; Li, Hongying; Zhang, Li; Tang, Jian (Frontiers in Pediatrics, 2022)
Background: Spastic paraplegia type 54 (SPG54) is a rare inherited autosomal recessive disorder, and a complex hereditary spastic paraplegia (HSP) caused by mutations in the phospholipase DDHD2 gene. SPG54 is characterized by early onset of spastic paraplegia, intellectual disability and dysplasia of corpus callosum. Case presentation: We report a 9 years and 5 months old Chinese girl with progressive spasm of the lower limbs, muscle weakness and intellectual disability. Brain magnetic resonance imaging (MRI) showed periventricular leukomalacia and thinning of the corpus callosum. According to the Wechsler Intelligence Scale, her IQ is 42. By whole exome sequencing, novel compound heterozygous missense mutations in the DDHD2 gene [c.168G>C, p.(Trp56Cys) and c.1505T>C, p.(Phe502Ser)] were identified in the proband. Comparative amino acid sequence alignment across different species revealed that Trp56 and Phe502 in the DDHD2 protein were highly conserved during evolution. And multiple in silico prediction tools suggested that both mutations were deleterious. Conclusions: Our study reports a very rare case of complicated HSP caused by two novel compound heterozygous mutations in the DDHD2 gene. Our findings expand the genetic spectrum of SPG54.